At odds : gambling and Canadians, 1919-1969 - Morton, Suzanne, 1961- (Heritage, 2003)
Using a rich variety of historical sources, Suzanne Morton traces the history of gambling regulation in five Canadian provinces - Nova Scotia, Quebec, Ontario, Manitoba, and B.C. - from the First World War to the federal legalization in 1969.